Pengembangan Program Bimbingan dan Konseling dalam Meningkatkan Keterampilan Sosial Siswa di Sekolah Dasar Taman Muda Ibu Pawiyatan Kota Yogyakarta - Usmani Haryanti; Abdul Rahim; Taryatman Taryatman (LP2M Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to develop a guidance and counseling program in improving students' social skills at SD TMIP Yogyakarta City. This is based on preliminary findings that indicate the social skills of students in these schools need to be improved. The research method used is Research & Development. The results of the development of guidance and counseling programs include: 1) development of service programs including a) network development, b) Development of Guidance and Counseling Management Activities, c) Service development, d) and types of services, 2) design and action plans include: a) identification, b) time management, c) inventory of needs and types of services, d) implementation, reflection and evaluation of programs.